2020
DOI: 10.1042/bsr20193169
|View full text |Cite|
|
Sign up to set email alerts
|

STEAP1 facilitates metastasis and epithelial–mesenchymal transition of lung adenocarcinoma via the JAK2/STAT3 signaling pathway

Abstract: Six-transmembrane epithelial antigen of prostate-1 (STEAP1) is a relatively newly identified gene target from prostate cancer, breast cancer, and gastric cancer. However, functions of STEAP1 in lung adenocarcinoma (LUAD) are still unknown. In the present study, we explored the molecular and cellular mechanisms of STEAP1 in LUAD. Western blot and Q-PCR were conducted to detect the protein and mRNA expressions respectively. The cell proliferation was tested by CCK8 assay. The effects of STEAP1 on the metastasis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…EMT, a process whereby epithelial cells gradually acquire a mesenchymal identity, is widely recognized to be involved in LUAD metastasis [ 18 ]. Most of the previous studies have focused on the functions and mechanisms of some ERGs [ 19 21 ]. However, ERG-based prognostic models have not been previously explored in LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…EMT, a process whereby epithelial cells gradually acquire a mesenchymal identity, is widely recognized to be involved in LUAD metastasis [ 18 ]. Most of the previous studies have focused on the functions and mechanisms of some ERGs [ 19 21 ]. However, ERG-based prognostic models have not been previously explored in LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…The elevated level of ROS is a salient feature of aggressive cancers like ES [ 49 , 50 ]. STEAP1 expression has been linked to increased cell proliferation, tumorigenicity, metastasis, and invasiveness in various cancers [ 22 , 23 , 24 , 27 ]. Previous studies have shown that STEAP1 overexpression leads to an increase in cytoplasmic and mitochondrial ROS levels in the ES [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is a 339 amino acid transmembrane protein implicated in cell adhesion, regulation of reactive oxygen species levels, and acts as an ion channel or transporter for cell–cell communication [ 24 ]. STEAP1 expression is highly upregulated in several cancers, including prostate, bladder, pancreas, ovary, gastrointestinal tract, cervix, and testicular cancer, as well as ES [ 25 , 26 , 27 , 28 , 29 ]. In the case of ES, STEAP1 is a direct transcriptional target of EWSFLI1 [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In other cancers, the JAK2/STAT3 signaling pathway is also implicated in cancer progression. In lung adenocarcinoma, JAK2/STAT3 pathway is also implicated in EMT and metastasis of cancer cells [55]. In melanoma, the anti-tumor effect of brevilin A also depends on the JAK2/STAT3 pathway [56].…”
Section: Discussionmentioning
confidence: 99%